Anxiety Level in Pencak Silat Extracurricular Students - Jumantara, Waraprada Anisa; Bafadal, Muhammad Facrurrozi; Ali, Rizki Hazazi (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aims to determine the level of pre-match anxiety in students. Students who take part in extracurricular pencak silat experience a decline in achievement, which is a very serious concern that needs to be studied based on the level of anxiety experienced by students before competing. Materials and methods. This study uses a quantitative research approach with descriptive research methods and survey research types. Data collection techniques used in this study include surveys (questionnaires) observation and documentation. The population in this study were 35 pencak silat extracurricular students and the sample obtained was 13 students using purposive sampling. Results. The results of the validity test there are 15 items declared entirely valid with the criteria r count> r table (0.553) then obtained the results of the reliability test which is 0.950> 0.90 which means the reliability value is perfect. The results showed that students who had a low anxiety level category were 1 student with a percentage of 7.7%, students who had an average anxiety level were 1 student with a percentage of 7.7% and students who had a high anxiety level were 11 people with a percentage of 84.6%. Conclusion. Based on the results of data analysis and discussion, it can be concluded that the Anxiety Level in Pencak Silat Extracurricular Students is in the ‘High’ category. This is because.